Effects of electrical stimulation, mixer type, processing time and mixing temperature on amount of protein extraction in mixed longissimus pork muscle - Huerta Leidenz, Nelson; Jerez Timaure, Nancy; Russell Cross, H. (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
Loins from 14 pig carcasses were randomly assigned to Electrical Stimulation (ES) treatments (sixteen loins stimulated and 11 loins .not stimulated) and processed either 2 h (hot processing), 48 h (conventional processing).or after 19 days (processing after aging) postslaughter. Twenty-five chunks of porcine longissimus dorsi samples, each providing constant volume and surface, were mixed one hour at 24ºC vs 4°C using two mixer types (models K-5A vs K-45 Kitchen-aid food preparers). Protein exudate formed on meat surfaces as a result of mixing muscle in the presence of 1% salt, 0.3% sodium tripolyphosphate and 5% water was collected to determine myofibrillar and sarcoplasmic protein extraction efficiency in relation to four different processing variables. Mixer type a significant (P Ë‚ .05) effect on exudate development and myofibrillar protein extractability. The model K-45, equipped with a smaller bowl capacity than the K-5A, developed a larger amount of exudate and extracted more myofibrillar protein (P Ë‚ .05) probably due to more frictional energy and agitation intensity. Sarcoplasmic protein concentration was lower (P Ë‚ .05) in the exudate recovered from non-stimulated samples and also from aged samples (P < .01). Mixing temperature did not affect (P Ë‚ .05) protein extractability. Processing time x mixer type and mixer type x mixing temperature interactions were significant (P < .05) for sarcoplasmic protein concentration in the exudates. Also, two-way (processing time x mixing temperature) and three-way interactions (ES x mixer type x mixing temperature) for the amount (mg) of myofibrillar protein extracted per gram of muscle were significant (P < .05) indicating the interdependence of al1 these treatments on the protein extractability variables. Some recommendations for similar studies are given in terms of the experimental procedure and protein extraction measurements.